Automation of Production Planning in the Context of Digitalization in the Aspect of Employees Continuing Education - Natalia, Popova; Daniil, Popov (KnE Social Sciences, 2021)
This article is devoted to continuing education and analysis of approaches to the study of the production planning automation process in the context of digitalization. The article contains the results of a survey of 40 employees of various industrial enterprises of one of the single-industry towns in the Urals. Employees combine work in the field of production and training at the university in engineering specialties. Respondents are students of evening and correspondence departments of the Ural Polytechnic Institute of the Ural Federal University named after the first President of Russia B.N. Yeltsin (a branch in the city of Kamensk-Uralsky). The aim of the research is an attempt to show that automation of operational planning of production at an industrial enterprise and the development of a system of personnel’ continuing education are the requirements of the very near future. The authors consider the initial basis the message that the establishment and development of professionalism of employees is possible when creating a system of continuous and advanced education. Theoretical research methods are the analysis of philosophical, managerial, sociological, pedagogical literature on the problem; systematic factual analysis; generalization; classification; and thought experiment. Empirical methods are the study and generalization of practical experience; questioning; qualitative and quantitative analysis of research results. Issues of researching ways to digitalize operational production planning at industrial enterprises are becoming increasingly relevant. The digital transformation of production is considered as a tool for collecting data that will be used to solve the tasks of operational planning of production using smart systems through built-in models and algorithms. The study has fixed that organizations need staff who are able to work in the context of digitalization and automation of the production process. Industrial enterprises create a system of continuous and advanced education. Such a system can function with the successful interaction of universities and enterprises. Employees of industrial enterprises who combine their professional activities with studying at a university are aware of the need to study during their life. Keywords: continuing education, digitalization, automation, workers, production planning